Stimulation of NADH-dependent microsomal DNA strand cleavage by rifamycin SV. - Kukiełka, E (1995)
Rifamycin SV is an antibiotic anti-bacterial agent used in the treatment of tuberculosis. This drug can autoxidize, especially in the presence of metals, and generate reactive oxygen species. A previous study indicated that rifamycin SV can increase NADH-dependent microsomal production of reactive oxygen species. The current study evaluated the ability of rifamycin SV to interact with iron and increase microsomal production of hydroxyl radical, as detected by conversion of supercoiled plasmid DNA into the relaxed open circular state. The plasmid used was pBluescript II KS(-), and the forms of DNA were separated by agarose-gel electrophoresis. Incubation of rat liver microsomes with plasmid plus NADH plus ferric-ATP caused DNA strand cleavage. The addition of rifamycin SV produced a time- and concentration-dependent increase in DNA-strand cleavage. No stimulation by rifamycin SV occurred in the absence of microsomes, NADH or ferric-ATP. Stimulation occurred with other ferric complexes besides ferric-ATP, e.g. ferric-histidine, ferric-citrate, ferric-EDTA, and ferric-(NH4)2SO4. Rifamycin SV did not significantly increase the high rates of DNA strand cleavage found with NADPH as the microsomal reductant. The stimulation of NADH-dependent microsomal DNA strand cleavage was completely blocked by catalase, superoxide dismutase, GSH and a variety of hydroxyl-radical-scavenging agents, but not by anti-oxidants that prevent microsomal lipid peroxidation. Redox cycling agents, such as menadione and paraquat, in contrast with rifamycin SV, stimulated the NADPH-dependent reaction; menadione and rifamycin SV were superior to paraquat in stimulating the NADH-dependent reaction. These results indicate that rifamycin SV can, in the presence of an iron catalyst, increase microsomal production of reactive oxygen species which can cause DNA-strand cleavage. In contrast with other redox cycling agents, the stimulation by rifamycin SV is more pronounced with NADH than with NADPH as the microsomal reductant. Interactions between rifamycin SV, iron and NADH generating hydroxyl-radical-like species may play a role in some of the hepatotoxic effects associated with the use of this antibacterial antibiotic.